PENGARUH LOKASI, KELENGKAPAN PRODUK, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN BELI KONSUMEN DI PAMELLA EMPAT YOGYAKARTA - Indri Hastuti Listyawati (Jurnal Bisnis, Manajemen, dan Akuntansi, 2017)
The purpose of this research is to examine the influence of location, product completeness, product quality and promotion to consumer buying decision at Pamella Fourof Yogyakarta. The population in this study is all consumers who shop at Pamella Four of Yogyakarta. Sample in this study are consumers who have been shopping at Pamella four for the last 4 months. While sampling in this research using purposive sampling and convenience sampling technique. Based on the tests that have been done, the result that the location affects consumer purchasing decision at Pamella Four Yogyakarta.While the completeness of product, product quality and promotion does not affect toconsumer buying decision at Pamella Four Yogyakarta. Keywords: location, completeness of product, product quality, promotion